2020
DOI: 10.1037/pspp0000272
|View full text |Cite
|
Sign up to set email alerts
|

Is well-being associated with the quantity and quality of social interactions?

Abstract: Social relationships are often touted as critical for well-being. However, the vast majority of studies on social relationships have relied on self-report measures of both social interactions and well-being, which makes it difficult to disentangle true associations from shared method variance. To address this gap, we assessed the quantity and quality of social interactions using both self-report and observer-based measures in everyday life. Participants (N = 256, 3,206 observations) wore the Electronically Act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
187
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(206 citation statements)
references
References 60 publications
14
187
2
3
Order By: Relevance
“…6 Thus, many of the very recommendations provided by the CDC to prevent the spread of COVID-19 7 may reduce critical social supports necessary for well-being. 6,8 Many other strategies for coping with stress, such as active coping to alleviate problems, have been shown to be helpful during a crisis; others, such as substance use coping, have been found universally maladaptive, and for still others, such as distraction, their utility may depend on the context. 9,10 Very little information is available regarding adherence to COVID-related CDC guidelines to prevent the spread of this disease.…”
mentioning
confidence: 99%
“…6 Thus, many of the very recommendations provided by the CDC to prevent the spread of COVID-19 7 may reduce critical social supports necessary for well-being. 6,8 Many other strategies for coping with stress, such as active coping to alleviate problems, have been shown to be helpful during a crisis; others, such as substance use coping, have been found universally maladaptive, and for still others, such as distraction, their utility may depend on the context. 9,10 Very little information is available regarding adherence to COVID-related CDC guidelines to prevent the spread of this disease.…”
mentioning
confidence: 99%
“…In an intensive study of over 250 college students, every participant reported feeling less socially connected, on average, following an hour without social interaction (compared to an hour that included social interaction; Sun, Harris, & Vazire, 2019). In another study, adults in Canada reported having six in-person interactions with close others and eleven interactions with strangers or acquaintances on a typical day, and they reported lower feelings of belonging on days when they had fewer interactions than usual (Sandstrom & Dunn, 2014).…”
mentioning
confidence: 99%
“…, and when people have more conversations with others, they report being happier (Sandstrom & Dunn, 2014b;Sun et al, 2019;Watson et al, 1992).…”
mentioning
confidence: 99%